Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Bài 2:
a, Ta có
\(3\sqrt{\left(-2\right)^2}+\sqrt{\left(-5\right)^2}\)
= \(3\left|-2\right|+\left|-5\right|\)
=\(6+5\)
= 11
Vậy \(3\sqrt{\left(-2\right)^2}+\sqrt{\left(-5\right)^2}=11\)
b, Ta có
\(\sqrt{6+2\sqrt{5}}-\sqrt{5}\)
= \(\sqrt{5+2\sqrt{5}+1}-\sqrt{5}\)
= \(\sqrt{\left(\sqrt{5}+1\right)^2}-\sqrt{5}\)
= \(\left|\sqrt{5}+1\right|-\sqrt{5}\)
= \(\sqrt{5}+1-\sqrt{5}=1\)
Vậy \(\sqrt{6+2\sqrt{5}}-\sqrt{5}=1\)
\(A=\frac{\sqrt{\left(x-1\right)^2}}{x-1}-\frac{\sqrt{\left(x-2\right)^2}}{x-2}=\frac{\left|x-1\right|}{x-1}-\frac{\left|x-2\right|}{x-2}\)
+) Nếu x < 1 => A = \(\frac{-\left(x-1\right)}{x-1}-\frac{-\left(x-2\right)}{x-2}=-1-\left(-1\right)=0\)
+) Nếu 1 < x < 2 => A = \(\frac{\left(x-1\right)}{x-1}-\frac{-\left(x-2\right)}{x-2}=1-\left(-1\right)=2\)
+) Nếu x > 2 => A = \(\frac{\left(x-1\right)}{x-1}-\frac{\left(x-2\right)}{x-2}=1-1=0\)